(untitled) (Journal of Science and Technology, 2016)
Maize is the most abundant cereal grown in Ghana and is accompanied by enormous amount of maize agrowastes. This waste which is currently underutilized can be used to produce bio-ethanol. Saccharification of lignocellulosic materials into simple sugars is a crucial and costly step towards bio-ethanol production from them. This work isolated cellulolytic fungi from soil sampled from Ejura farms which can efficiently hydrolyse maize agrowastes. Ten of the isolates exhibited cellulase activities when screened on Mandel’s agar media. Aspergillus niger had the highest significant filter paper activity, carboxymethyl cellulose activity and protein concentra-tion of 0.37 FPU/ml 0.7025 U/ml and 5.62 mg/ml respectively when the cellulolytic isolates were assayed on corncob based broth media.